(3TQM dQjGV GdeSGFds - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg (B... (3bhdg CeG GdeWdb hgh eG jSJMb GWdGb GdGSe ef Ohf Jhba Ydi GdEVGaI hdG jNQLg Yf hbhY GdJbjjO HgG aj HYV GdCaQGO Cbhd hPdc dCf GdeQGO HGSJMbGb GWdGb GdGSeg Gfg dh GWdb Ydjg (B...s
(3BNQgG (B:s
... (3GdKGfj CUGdI YOe dMaGX GdNUhUjI aj Gdhbha Ydjg bjO hYOe GYJHGQ GdPchQjI ajg YfhGfG hajg ChdG Cfg eKdK Ldj hbGfjg Cfg eYGQV HGdeKd HOjgI Gfg ceG Gf GdGNJUGU (B... (3dG jLhR dCLO ef ZjQ gPjf GdUfajf GdJUQa ajgG jbjfG (B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis